Using herbs medically without knowing their composition: are we playing Russian roulette?. (4th May 2022) - Kohn, Orly F.; Lew, Susie Q.; Wong, Steve Siu-Man; Sam, Ramin; Chen, Hung-Chun; Raimann, Jochen G.; Leehey, David J.; Tzamaloukas, Antonios H.; Ing, Todd S.
Abstract: Herbal medicine, a form of complementary and alternative medicine (CAM), is used throughout the world, in both developing and developed countries. The ingredients in herbal medicines are not standardized by any regulatory agency. Variability exists in the ingredients as well as in their concentrations. Plant products may become contaminated with bacteria and fungi during storage. Therefore, harm can occur to the kidney, liver, and blood components after ingestion. We encourage scientific studies to identify the active ingredients in herbs and to standardize their concentrations in all herbal preparations. Rigorous studies need to be performed in order to understand the effect of herbal ingredients on different organ systems as well as these substances' interaction with other medications.